2017
DOI: 10.1007/s10067-017-3893-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of air pollution on airway inflammation and disease activity in childhood-systemic lupus erythematosus

Abstract: Exposure to fine particles may trigger pulmonary inflammation/systemic inflammation. The objective of this study was to investigate the association between daily individual exposure to air pollutants and airway inflammation and disease activity in childhood-onset systemic lupus erythematosus (cSLE) patients. A longitudinal panel study was carried out in 108 consecutive appointments with cSLE patients without respiratory diseases. Over four consecutive weeks, daily individual measures of nitrogen dioxide (NO), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 41 publications
0
34
0
1
Order By: Relevance
“…All these modifications are well known to contribute to atherogenesis, chronic respiratory diseases and cardiovascular events, the latter strictly correlated with IL-6 serum levels (Aromolaran et al, 2018). Nevertheless, aside of "classical" pollution-related conditions, several recent studies have pointed out a possible correlation between poor air quality and development and worsening of chronic inflammatory disease, such as systemic lupus erythematous (Alves et al, 2018;Gulati and Brunner, 2018) and rheumatoid arthritis (Sigaux et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All these modifications are well known to contribute to atherogenesis, chronic respiratory diseases and cardiovascular events, the latter strictly correlated with IL-6 serum levels (Aromolaran et al, 2018). Nevertheless, aside of "classical" pollution-related conditions, several recent studies have pointed out a possible correlation between poor air quality and development and worsening of chronic inflammatory disease, such as systemic lupus erythematous (Alves et al, 2018;Gulati and Brunner, 2018) and rheumatoid arthritis (Sigaux et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmunity can result from antibodies produced against Borrelia that cross react with our own tissue antigens (molecular mimicry), while bacteria activate Toll-like receptor 2 (TLR-2), [160,161] furthering increases in the pro-inflammatory cytokines, TNF-alpha and IL-17. Similarly, mercury (Hg), bisphenol A (BPA), asbestos, and small particle pollution have now been published in the medical literature as potential factors increasing autoimmune reactions [37,51,101,102]. Over 84% of patients had evidence of exposure to at least one heavy metal, with 68% had evidence of mercury exposure; 100%, 46.5%, and 82% of patients had evidence of exposure to Borrelia , Bartonella , and Mycoplasma spp., respectively; and 72.5% of our patients in this study had evidence of immune dysfunction, including production of positive antinuclear antibodies and rheumatoid factors.…”
Section: Discussionmentioning
confidence: 99%
“…Any of these chronic disease manifestations may be worsened and/or due to one or multiple factors. This is the case with autoimmune reactions, which the scientific literature has shown can be affected by exposure to borrelia and other infections [100] (including, but not limited to, Bartonella and Mycoplasma species) [30,32,33], environmental toxin exposure (i.e., mercury, bisphenol A, asbestos, and/or small particle pollution) [50,51,101,102], imbalances in the microbiome of the gut, and/or from a genetic predisposition [103]. We therefore collected data from an online survey, which evaluated the efficacy of dapsone combined with other antibiotics and agents that disrupt biofilm for the treatment of chronic Lyme disease/PTLDS, along with information data mined directly from 200 patient records detailing abnormalities on the MSIDS model.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, COVID-19 infection can cause pneumonia and acute respiratory syndrome, i.e., symptoms that can be exacerbated by air pollution. Although not directly connected to COVID-19 diffusion, previous research has suggested a correlation between poor air quality and development and worsening of chronic inflammatory disease (Alves et al, 2018). Since COVID-19 is mainly a respiratory syndrome, polluted air was supposed to increase the risk of death of infected patients, mainly due to the high concentrations of airborne PM (Paital, 2020, in press).…”
Section: Introductionmentioning
confidence: 99%